Modal expansion approach for accurately computing resonant modes in a high‐Q optical resonator. Issue 2 (February 2014) - Kang, Young Mo; Xue, Mingfeng; Arbabi, Amir; Jin, Jian‐Ming; Goddard, Lynford L.
ABSTRACT We present a method based on the modal expansion approach for computing resonant modes of a high‐Q optical resonator. We reconstruct both the complex eigenfrequencies and the spatial modal profiles by solving an inhomogeneous linear system excited by a current source in the resonator. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:278–284, 2014